NGS Analysis of Human Embryo Culture Media Reveals miRNAs of Extra Embryonic Origin. (February 2019) - Sánchez-Ribas, Immaculada; Diaz-Gimeno, Patricia; Quiñonero, Alicia; Ojeda, María; Larreategui, Zaloa; Ballesteros, Agustín; Domínguez, Francisco
Our objective in this work was to isolate, identify, and compare micro-RNAs (miRNAs) found in spent culture media of euploid and aneuploid in vitro fertilization (IVF) embryos. Seventy-two embryos from 62 patients were collected, and their spent media were retained. A total of 108 spent conditioned media samples were analyzed (n = 36 day 3 euploid embryos, n = 36 day 3 aneuploid embryos, and n = 36 matched control media). Fifty hed-control media embryos were analyzed using next-generation sequencing (NGS) technology. We detected 53 known human miRNAs present in the spent conditioned media of euploid and aneuploid IVF embryos. miR-181b-5p and miR-191-5p were found the most represented. We validated our results by quantitative polymerase chain reaction (qPCR), but no significant results were obtained between the groups. In conclusion, we obtained the list of miRNAs present in the spent conditioned media from euploid and aneuploid IVF embryos, but our data suggest that these miRNAs could have a nonembryonic origin.